Green geopolymer concrete incorporating local incineration ash - Ho, Jia Sing. (2012)
This paper studies the usage of local incineration fly ash as a material for synthesizing geopolymer concrete. X-Ray diffraction, X-Ray Fluorescence and particle size analysis were conducted on the materials that were used in the mixture. A combination of sodium hydroxide and sodium silicate solution was used as alkali activator. Molarity of the sodium hydroxide used was 16 M. Incineration fly ash geopolymer were synthesized with different water to ash ratio of 0.5, 0.7 and 0.9 and subjected to room temperature curing. The highest 7 days compressive strength obtained was 5.28 MPa at water to ash ratio of 0.9. To increase the strength further, 20% of incineration bottom ash, metakaolin and slag were added to the incineration fly ash geopolymer at water to ash ratio 0.9 with two types of curing (room temperature and oven curing at 900C). Out of the 3 materials added, the highest 7 days compressive strength was achieved by using 20% slag at oven curing. More mixtures were synthesize using slag in different proportion of 40%, 60%, 80 % and 100 % keeping the water to ash ratio at 0.9 and molarity of sodium hydroxide at 16 M. It was noted that when the proportion of slag increases, the compressive strength also increases. 60% slag and 40% incineration fly ash geopolymer was able to achieve 7 days compressive strength of 20.92 MPa at oven curing.